Respuesta :

Answer:

u = -24/7

Step-by-step explanation:

u = 6 = u

v      -7     4

-7u = 24

u = -24/7

Answer:

u = - [tex]\frac{24}{7}[/tex]

Step-by-step explanation:

Given that u varies directly with v then the equation relating them is

u = kv ← k is the constant of variation

To find k use the condition u = 6 when v = - 7, then

6 = - 7k ( divide both sides by - 7 )

- [tex]\frac{6}{7}[/tex] = k

u = - [tex]\frac{6}{7}[/tex] v ← equation of variation

When v = 4 , then

u = - [tex]\frac{6}{7}[/tex] × 4 = - [tex]\frac{24}{7}[/tex]

ACCESS MORE